Sustainable hydrogen production and CO2 mitigation from acetic acid dry reforming over Ni/Al2O3 catalyst - Nguyen, Anh-Tam; Ng, Kim Hoong; Kumar, Ponnusamy Senthil; Pham, Thuy-Phuong T.; Herma Dina, Setiabudi; Mohammad Yusuf, .; Pham, Le Kim Hoang; Show, Pau Loke; Hussain, Ijaz; Vo, Dai-Viet N. (Elsevier Ltd, 2024)
Dry reforming of acetic acid (DRA) was first-time investigated on 10%Ni/Al2O3 at varied temperatures within 923–973 K employing several CO2:CH3COOH ratios of 1.5:2; 1:1; and 2:1. Depending on NiO particle size and location on support surface or inside the porous support structure, the H2 reduction of NiO phase to active metallic Ni0 form was evidenced at different reduction temperatures within 550–950 K and the estimated degree of reduction was about 73.68%. Weak, medium, and strong basic centres were evidenced on 10%Ni/Al2O3 via CO2 desorption measurement. Increasing DRA temperature improved both CH3COOH and CO2 conversions with the corresponding apparent activation energy of 100.71 and 58.50 kJ mol−1. As CO2 partial pressure was increased from 0 to 40 kPa, the initial CH3COOH conversion was noticeably enhanced from 30.5% to 97.8% whilst H2/CO ratio always remained less than unity (0.73–0.77). Notably, DRA was a two-step process and barely negligible CH4 intermediate product was evidenced since it was promptly reformed by CO2 into syngas. The Ni0 active form was not susceptible to oxidation during DRA and carbon deposited on spent catalyst surface was heterogeneous in nature with the evident co-existence of amorphous and graphitic carbons.